Relación entre el tipo de transporte y la productividad laboral de los trabajadores del sector formal de Ecuador durante el 2017 - Vivanco Palacios, Auria Yadira (2024)
Currently, labor productivity is measured by a series of factors that can have a negative or positive impact both at the individual level and on the economy in general. In Ecuador, between June 2007 and June 2017, the country's productivity level reported an increase of only 1.78%. Therefore, the general objective of this research work is to evaluate the relationship between the type of transportation and labor productivity of workers in Ecuador's formal sector during 2017, through the use of statistical and econometric techniques, in order to propose public policies that help increase labor productivity levels. For this purpose, data from the National Institute of Statistics and Census [INEC], from 2017 were used; a multiple linear regression model was applied to find out the relationship between labor productivity and type of transportation, and an Oaxaca (1973) and Blinder (1973) model was applied to evidence the productivity gap between workers using public and private transportation. The main findings suggest that individuals who use public transportation, have higher education, are male, are between 30 and 60 years old, are public employees, have an appointment, are affiliated with the IESS or ISSFA, work in companies with more than 100 workers, and have work experience between 30 and 44 years are more productive. In addition, the existence of a productivity gap in favor of people who use public transportation was confirmed, which is mostly explained by non-observable factors. Therefore, it is recommended that the government establish rigorous norms that guarantee compliance with the working conditions of workers and promote policies that improve access to public transportation and allocate greater investment in transportation infrastructure.